Dengue Patients Exhibit Higher Levels of PrM and E Antibodies Than Their Asymptomatic Counterparts - Yeo, A.S.L.; Rathakrishnan, A.; Wang, S.M.; Ponnampalavanar, S.; Manikam, R.; Sathar, J.; Kumari Natkunam, S.; Sekaran, S.D. (Hindawi Publishing Corporation, 2015)
Dengue virus infection is a common tropical disease which often occurs without being detected. These asymptomatic cases provide information in relation to the manifestation of immunological aspects. In this study, we developed an ELISA method to compare neutralizing effects of dengue prM and E antibodies between dengue patients and their asymptomatic household members. Recombinant D2 premembrane (prM) was constructed, cloned, and tested for antigenicity. The recombinant protein was purified and tested with controls by using an indirect ELISA method. Positive dengue serum samples with their asymptomatic pair were then carried out onto the developed ELISA. In addition, commercially available recombinant envelope (E) protein was used to develop an ELISA which was tested with the same set of serum samples in the prM ELISA. Asymptomatic individuals showed preexisting heterotypic neutralizing antibodies. The recombinant prM was antigenically reactive in the developed ELISA. Dengue patients had higher prM and E antibodies compared to their household members. Our study highlights the neutralizing antibodies levels with respect to dengue prM and E between dengue patients and asymptomatic individuals.